The Palestine Occupation and Its Impact to Millennial’s Intention to Boycott Israeli Related Products in Indonesia - Anita Priantina; Putri Syifa Amalia (Tazkia Islamic Finance and Business Review, 2025)
This study examines the impact of Palestine’s occupation on Indonesian millennials' intentions to boycott Israeli-affiliated products, focusing on attitude, perceived behavioral control, and subjective norm as determinants. Millennials are chosen as the research object based on the assumption that they represent an active workforce with relatively higher financial capability, potentially increasing their influence on consumer behavior. Using Structural Equation Modeling-Partial Least Squares (SEM-PLS), findings reveal that attitude and perceived behavioral control significantly impact boycott intention, while subjective norm is not significant. These results indicate that millennials are more influenced by personal beliefs and self-efficacy than by social pressures. Policy recommendations include enhancing educational campaigns to strengthen individual attitudes and empower millennials with resources for informed choices, possibly through collaborations with influencers and educational institutions. Future studies could explore additional factors, such as media influence and availability of alternatives, to provide a broader understanding of boycott behavior among millennials.